THE CONTRADICTION BETWEEN LIBERALISM AND DEMOCRACY IN THE PERSPECTIVE OF POLITICAL PHILOSOPHY - Valantiejus, Vaidotas (Politologija, 2015)
The main strategy of this article is to consider liberalism in contrast withdemocracy. Many critics of liberal democracy argue that there is no necessaryrelation between two distinct traditions but only a contingent historicalarticulation. The main ideas of liberalism are the rule of law, the defense ofhuman rights and the respect of individual liberty. Democracy, by contrast,relies on substantial equality, identity between governing and governed, andpopular sovereignty. In other words there is a tension between democratichomogeneity and liberal heterogeneity or pluralism.Mainly because of liberal assumption of an autonomous rights bearingindividual, liberalism is very skeptical on the issue of democracy. Liberalsstress the protection of freedom against potential oppressive democraticmajorities. Equality in the liberal tradition is reduced to equal liberty. Theabstract liberal conception of equality postulates that every person is, as aperson, morally equal to every other person. The substantial democratic conception of equality, however, requires the possibility of inequality, i.e. thepossibility of distinguishing who belongs to the demos and who is exterior toit. Equality is only valuable politically so long as it has substance or concretepolitical context.John Rawls’s theory of political liberalism accents formal and proceduralaspects of liberal democracy. The main cause is that Rawls’s theory is deontological.He draws the distinction between the “right” and the “good” – between a framework of basic rights and liberties, and the conceptions of the good that people may choose to pursue within this framework. Rawls’s priority of the right over the good is presented as the principle of neutrality.But the problem is that political liberalism can provide a consensus onlyamong reasonable persons who are persons who accept the principles ofpolitical liberalism. Thus Rawls’s allegedly neutral public reason is derivedfrom the fundamentals of liberalism or the specific concept of good.Communitarian political philosophy criticizes liberalism for itsatomism, concept of negative liberty and the priority of human rights. Deontological liberalism, it is said, is excessively individualistic, abstract and universalistic. Challenging the liberal commitment to individualism and to human rights, communitarians insist that democratic community cannot be justified without reference to common purposes and ends. To be a citizen is to interpret oneself as a member of the polity. Democratic homogeneity requires the identity between governing and governed. So, democracy rests not on individual rights, but essentially on the general will of the community.The model of deliberative democracy argues that the essence of democracy is deliberation itself, as opposed to voting, interest aggregation, constitutional rights, or self-government. Deliberative democracy concerns the degree to which democratic control is substantive and engaged by competent citizens. The influence of informal public opinion formation, it is claimed, has to be transformed into “communicative power” and accordingly into “administrative power”. But in essence deliberative theory accepts the key tenets of political liberalism. Some deliberative theorists argue that the priority of liberal rights is necessary for deliberative democracy itself.The agonistic model of democracy says that the dimension of antagonism is inherent in human relations. The ineradicability of antagonism, it is argued, is constitutive of the political. The main task of this model is to establish us/them discrimination in a way that is compatible with pluralist democracy. On the one hand, agonistic democracy criticizes neutral and procedural aspects of liberal democracy, on the other hand, both agonistic and liberal models accepts the priority of pluralism and individual rights.In summary, the processes of liberalization and democratization are conceptually contradictory. The ethos of liberalism, especially the ideal of negative liberty, reduces the substantial concept of equality to indifferent equal liberty. The principle of moral equality is gradually transformed to the principle of moral individualism. The deontological liberalism ignores the main democratic question – how to establish the democratic community with both the autonomy of persons and the shared understanding of the good? In this way political liberalism negates the ideal of democracy – the identity between governing and governed.